Myeloperoxidase-Dependent LDL Modifications in Bloodstream Are Mainly Predicted by Angiotensin II, Adiponectin, and Myeloperoxidase Activity: A Cross-Sectional Study in Men. (18th November 2013) - Zouaoui Boudjeltia, Karim; Delporte, Cédric; Van Antwerpen, Pierre; Franck, Thierry; Serteyn, Didier; Moguilevsky, Nicole; Raes, Martine; Vanhamme, Luc; Vanhaeverbeek, Michel; Van Meerhaeghe, Alain; Roumeguère, Thierry
Abstract : The present paradigm of atherogenesis proposes that low density lipoproteins (LDLs) are trapped in subendothelial space of the vascular wall where they are oxidized. Previously, we showed that oxidation is not restricted to the subendothelial location. Myeloperoxidase (MPO), an enzyme secreted by neutrophils and macrophages, can modify LDL (Mox-LDL) at the surface of endothelial cells. In addition we observed that the activation of the endothelial cells by angiotensin II amplifies this process. We suggested that induction of the NADPH oxidase complex was a major step in the oxidative process. Based on these data, we asked whether there was an independent association, in 121 patients, between NADPH oxidase modulators, such as angiotensin II, adiponectin, and levels of circulating Mox-LDL. Our observations suggest that the combination of blood angiotensin II, MPO activity, and adiponectin explains, at least partially, serum Mox-LDL levels.